Taṭbīq taʿlīm mahārat al-istimāʿ bi-ṭarīqah al-muḥāḍarah li-ṭullāb al-faṣl al-sābiʿ fī al-madrasah al-tsanawiyah "Bābu al-Salām" Tambar Jogoroto Jombang - Elok Istighfarin; Muâ€™at (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
Education experts recognize the need to use the method as an educational medium or as a teaching and learning technique. This shows that in the learning method, a student can be more interested in learning. The purpose of this study was to determine the implementation of maharah istima learning with the lecture method in the seventh grade of Mts Babussalam Tambar Jogoroto Jombang school. This study uses a qualitative research data sourced from observations, interviews and documents. The result of the research is that this lecture method has been carried out since elementary school. Most of the children who go up to the MTs level are graduates of MI BBs themselves, so the use of this lecture method is familiar to them. For some children who are not graduates of MI BBS, this special maharah learning method is considered easier and very helpful for their understanding. The advantages of the lecture method: it is simpler, does not require a projector/machine, and it is easier to control the class. And the drawbacks of this method are: it tends to be directed by the teacher, tends to position itself as a listener and a writer. students will be more bored and sleepy.